2014
DOI: 10.1158/0008-5472.can-13-2020
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Estrogen Receptor α Expression in Breast Cancer Cells by Metastasis-Associated Protein 1

Abstract: Metastasis-associated protein 1 (MTA1) is a component of the nucleosome remodeling and histone deacetylase (HDAC) complex, which plays an important role in progression of breast cancer. Although MTA1 is known as a repressor of the transactivation function of estrogen receptor a (ERa), its involvement in the epigenetic control of transcription of the ERa gene ESR1 has not been studied. Here, we show that silencing of MTA1 reduced the level of expression of ERa in ERa-positive cells but increased it in ERa-negat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 43 publications
(54 reference statements)
4
75
0
Order By: Relevance
“…Though IFI16 is known to be involved in transcriptional regulation [32][34], [48], [70][76], the mechanisms of this regulation have been largely undetermined. IFI16 may modulate transcription through association with transcription factors and/or blocking their association with promoters [33], [34], [45], [48], [70], [72][74] or it may promote the formation of heterochromatin on promoters, resulting in their repression [38], [76].…”
Section: Discussionmentioning
confidence: 99%
“…Though IFI16 is known to be involved in transcriptional regulation [32][34], [48], [70][76], the mechanisms of this regulation have been largely undetermined. IFI16 may modulate transcription through association with transcription factors and/or blocking their association with promoters [33], [34], [45], [48], [70], [72][74] or it may promote the formation of heterochromatin on promoters, resulting in their repression [38], [76].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR analysis for early viral transcripts showed that their expression was significantly lower in AdVIFI16-infected cells than in AdVLacZ-infected cells, especially at 48 h. The observed effect of IFI16 on the integrated HPV genome is consistent with its activity on viral and cellular promoters alongside its interaction with histone modification machinery. Indeed, IFI16 has been demonstrated to induce changes in markers for heterochromatin and euchromatin on viral and cellular promoters (21,33,51).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the results of the present study demonstrated that TAC chemotherapy combined with endocrine MPA therapy may effectively improve the prognosis and survival rates of patients with endometrial cancer. MTA1 is associated with the metastatic state in various types of cancer (9)(10)(11)(12)(13)(14)(15). For example, recent studies have demonstrated that MTA1 promotes tumor invasion in human esophageal (11) and laryngeal (14) squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…MTA1 is associated with the metastatic state in various types of cancer (9)(10)(11)(12)(13)(14)(15). For example, recent studies have demonstrated that MTA1 promotes tumor invasion in human esophageal (11) and laryngeal (14) squamous cell carcinoma cells. In the present study, it was identified that combined use of MPA and TAC chemotherapy may significantly decrease the expression levels of MTA1 in patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation